2013
DOI: 10.1371/journal.pone.0066781
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Glycation End Products Induce Human Corneal Epithelial Cells Apoptosis through Generation of Reactive Oxygen Species and Activation of JNK and p38 MAPK Pathways

Abstract: Advanced Glycation End Products (AGEs) has been implicated in the progression of diabetic keratopathy. However, details regarding their function are not well understood. In the present study, we investigated the effects of intracellular reactive oxygen species (ROS) and JNK, p38 MAPK on AGE-modified bovine serum albumin (BSA) induced Human telomerase-immortalized corneal epithelial cells (HUCLs) apoptosis. We found that AGE-BSA induced HUCLs apoptosis and increased Bax protein expression, decreased Bcl-2 prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
52
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 55 publications
7
52
0
1
Order By: Relevance
“…These concentrations of AGE-BSA are within the range used in many other studies (e.g. Nah et al (2007), Shen et al (2010), Okazaki et al (2012) and Shi et al (2013)). …”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…These concentrations of AGE-BSA are within the range used in many other studies (e.g. Nah et al (2007), Shen et al (2010), Okazaki et al (2012) and Shi et al (2013)). …”
Section: Resultssupporting
confidence: 64%
“…The apoptosis of various cell types caused by AGEs involves the activation of the p38 MAPK pathway (Shen et al 2010, Shi et al 2013), and we found that this pathway also participates in AGE-BSA-induced BMSC apoptosis. It is probably not the only MAPK pathway involved, since we were unable to completely abrogate the apoptosis of BMSCs with the p38 inhibitor.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…ROS was reported as the upstream signal molecule of p38 MAPK, directly regulating the phosphorylation of p38, and ultimately affecting biological effect. [38][39][40][41] However, some studies demonstrated contrary views. [42][43][44] The different regulation networks may cause varied biological effects in diverse cells and organisms.…”
Section: Discussionmentioning
confidence: 99%
“…To mimic the pathological process of kidney disease induced by diabetes mellitus, the human renal tubular epithelial cell line HK-2 was exposed to AGE-BSA in vitro. The AGE-BSA concentration at 100 g/ml was utilized, because this dose was reported to represent AGEs level in the serum of diabetic patients (17). Before incubation with AGE-BSA, only a few LC3-II puncta were detected in the HK-2 cells through immunofluorescence staining (Fig.…”
Section: Autophagic Vacuoles Are Accumulated In Tecs During the Progrmentioning
confidence: 99%